Simulation of fatigue crack propagation in the wing main spar flange - Augustin, Petr (Vysoké učení technické v Brně, Fakulta strojního inženýrství, 2019)
Simulation of fatigue crack growth in the bottom flange of twin turboprop commuter aircraft wing spar is described in this paper. Analysed crack propagation scenario represents real wing full-scale fatigue test failure. Computational model of bottom flange was prepared using three-dimensional fracture mechanics software FRANC3D. Calculation of crack growth under the variable amplitude loading was performed in AFGROW code using the NASGRO equation and Wheeler retardation model. It was verified with the results of wing spar specimen fatigue test and fractograpic analysis of fatigue fracture from this experiment. Computational model was applied in the prognostic algorithm of structure health monitoring system.
Keywords: fatigue crack growth; wing spar; fatigue test; BEM; SHM